Relief Tiles from Halich: A Problem of Samples’ Searching - Matveev, Vasilii N. (Actual Problems of Theory and History of Art, 2019)
The aim of this report is to analyze the relief tiles from Halich in the wide context of applied art and architecture décor, to find the possible provenance of the craftsmen who produced them.All the relief tiles can be divided into two types, which differ in morphology (dimensions, peculiaritiesof clay mass) and style of images. Tiles of the first type are smaller, the draft is schematic, consists of outercounter line and a few inner lines. They were typical of Old Rus’ architecture by their size and shape, were produced by local craftsmen, who worked according to the local art tradition and used the motifs which they could see on the kolts.Tiles of the second type were bigger, they had not a counter but a real relief image on them, so that the picture distinctly stands out from the tile. The drawing was made carefully, with many peculiar details. Generally, the motives represented on these tiles are definitely connected with the Romanesque architectural reliefs.Tiles of the second type are a part of the European art tradition, especially their morphology is typical of European building ceramic. They were made by the foreign craftsmen, but in this case they were made in a special manner, which isn’t the same as the west analogues.The peculiarities of images of the Halich tiles confirm the conclusions drawn from the analysis of morphology.The tiles of the first type are related to the local tradition of Old Rus, the tiles of the second type belong to the imported, West European, Romanesque tradition.
Keywords: ceramic tiles; Halich; fantastic creatures; Romanesque reliefs; décor